2006
DOI: 10.1186/1472-6963-6-73
|View full text |Cite
|
Sign up to set email alerts
|

Two years of psychogeriatric consultations in a nursing home: reasons for referral compared to psychiatrists' assessment

Abstract: BackgroundIn spite of the high prevalence of psychiatric disorders among elderly residents in nursing homes, only a small number of patients in need of specialist care are referred to a psychiatric consultant. The aim of this research was to evaluate the consultation activity and the appropriateness of referral to psychiatric assessment.MethodsData were collected and analysed on consultation carried out over a two-year period in a RSA (Residenza Socio-Assistenziale) in Northern-Italy. Data were catalogued with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2007
2007
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Although this procedure enabled us to mimic psychiatric consultation as it happens in everyday clinical practice, it also means that our data on referrals are not exactly the same as estimates of actual symptom prevalence. Nevertheless, our findings are consistent with those of others (Rovner et al, 1990;Loebel et al, 1991;Shea et al, 1994;Leo et al, 2002;Callegari et al, 2006), which may imply that by and large validity is not challenged.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although this procedure enabled us to mimic psychiatric consultation as it happens in everyday clinical practice, it also means that our data on referrals are not exactly the same as estimates of actual symptom prevalence. Nevertheless, our findings are consistent with those of others (Rovner et al, 1990;Loebel et al, 1991;Shea et al, 1994;Leo et al, 2002;Callegari et al, 2006), which may imply that by and large validity is not challenged.…”
Section: Discussionsupporting
confidence: 92%
“…That study did not specify apathy as a separate behavioural change category. An Italian study in residential care facilities showed that psychiatric referrals were associated with symptoms of depression (17.2%), psychosis (14%), agitation (34.8%), aggression (23.5%) and sleep disturbances (6.8%) (Callegari et al, 2006). A large scale study showed that nursing home residents who stole, hurt themselves, exposed themselves or hallucinated were more likely to receiving specialist mental health services (Shea et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, less than half received other outpatient behavioral health services. While the reason for underutilization of behavioral health services for any one individual is unknown, the general finding of underutilization of behavioral health services in nursing home settings has been well documented (Reichman et al, 1998;Callegari et al, 2006). Reported reasons for this include lack of access, inadequate resources, inadequate reimbursement rates, or staff attitudes toward NH residents with mental health disorders (Reichman et al, 1998;Hsu et al, 2004;Callegari et al, 2006).…”
Section: Discussionmentioning
confidence: 93%